Application of Rabbit Urine and Manure Based Fertilizer on the Growth of Arabica and Robusta Coffee Seedlings - Prajanti, Sucihatiningsih Dian Wisika; Litaay, Christina; Widiatningrum, Talitha; Amelia, Dhea Rizky; Daud, Dalila (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Coffee farming demands substantial amounts of fertilizer. Furthermore, the expensive cost of chemical fertilizers prompt coffee growers to seek alternative remedies. One emerging solution is the utilization of organic fertilizer. This study aims to assess the impact of organic fertilizer, specifically made from rabbit manure and urine, on the growth of Arabica and Robusta coffee seedlings. The experiment focused on the context of coffee cultivation in Temanggung Regency, comparing the effects with goat manure fertilizer. The method was initiated by producing organic fertilizer, encompassing rabbit manure, goat manure, and rabbit urine. Then, the fertilizer was applied to Arabica and Robusta seedlings. The research employs quantitative and descriptive analyses. Quantitative data encompasses the nutrient content of each fertilizer and soil, plant height, leaves number, and stem diameter. Descriptive analysis involves the overall performance evaluation. The application of rabbit manure and urine as fertilizers to Arabica and Robusta coffee seedlings yields positive outcomes, i.e. enhancing plant height, leaves number, and seedling diameter. Among the tested organic fertilizers, rabbit urine notably influenced the plant height, leaves number, and stem diameter of both seedlings. The performance of the rabbit urine treatment exhibited healthier attributes compared to those without any fertilizer, such as sturdy leaves and robust stems. Additionally, the root systems of the untreated plants appear less vigorous with sparser root hairs.